Makna Mawar dan Melati dalam Sajak dan Lagu Sebuah Analisis Wacana tentang Metafora - Abu Katili, Adriansyah (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
This article contains a discourse analysis of the meaning of roses and jasmine in songs and poems. The poem analyzed is "The Sick Rose" by William Blake. The songs analyzed are "Bunga Mawar" by The Mercy's and "Melati Putih" by Bimbo. The analysis was carried out using the theory of metaphor proposed by Lakoff. The theory states that metaphor is a way of thinking to sharpen the perception of reality. This analysis is a content analysis that is carried out qualitatively. By applying the method of metaphor analysis and the principles of discourse analysis, it is concluded that the meaning of roses in the poem The Sick Rose by William Blake and "Melati Putih" sung by Bimbo have the same sense, namely the destruction of love because those who come to love destroy it. In the song "Mawar" by The Mercy's roses are a metaphor for love, beautiful girls, and love that cannot be achieved. The author also found that metaphor is not only a way of thinking as proposed by Lakoff, but also a means of expressing emotions.